A Real-Time PCR Method to Detect the Population Level of Halovirus SNJ1. - Yunjun Mei (PLoS ONE, 2016)
Although viruses of haloarchaea are the predominant predator in hypersaline ecosystem, the culture studies about halovirus-host systems are infancy. The main reason is the tradition methodology (plaque assay) for virus-host interaction depends on culturable and susceptible host. Actually, more than 90% of haloarchaea are unculturable. Therefore, it is necessary to establish an approach for detecting the dynamics of virus in hypersaline environment without culture. In this study, we report a convenient method to determine the dynamics of halovirus SNJ1 based on quantitative real-time PCR (qPCR). All findings showed that the qPCR method was specific (single peak in melt curves), accurate (a good linear relationship between the log of the PFU and the Ct values, R2 = 0.99), reproducible (low coefficient of variations, below 1%). Additionally, the physicochemical characteristics of the samples tested did not influence the stability of qPCR. Therefore, the qPCR method has the potential value in quantifying and surveying haloviruses in halophilic ecological system.